In vitro anticancer activity of loquat tea by inducing apoptosis in human leukemia cells. Issue 10 (3rd October 2014) - Zar, Phyu Phyu Khine; Yano, Satoshi; Sakao, Kozue; Hashimoto, Fumio; Nakano, Takayuki; Fujii, Makoto; Hou, De-Xing
Abstract: Fresh loquat leaves have been used as folk health herb in Asian countries for long time, although the evidence supporting their functions is still minimal. This study aimed to clarify the chemopreventive effect of loquat tea extract (LTE) by investigating the inhibition on proliferation, and underlying mechanisms in human promyelocytic leukemia cells (HL-60). LTE inhibited proliferation of HL-60 in a dose-dependent manner. Molecular data showed that the isolated fraction of LTE induced apoptosis of HL-60 as characterized by DNA fragmentation; activation of caspase-3, -8, and -9; and inactivation of poly(ADP)ribose polymerase. Moreover, LTE fraction increased the ratio of pro-apoptotic Bcl-2-associated X protein (Bax)/anti-apoptotic myeloid cell leukemia 1 (Mcl-1) that caused mitochondrial membrane potential loss and cytochrome c released to cytosol. Thus, our data indicate that LTE might induce apoptosis in HL-60 cells through a mitochondrial dysfunction pathway. These findings enhance our understanding for chemopreventive function of loquat tea. Graphical abstract: : Schematic molecular mechanism of loquat tea-induced apoptosis in HL-60 cells which involves a mitochondrial dysfunction pathway